Adat Law as An Alternative Option In Law Pluralism Perspective In Indonesia - Sulastriyono, Sulastriyono; APHA, Journal Manager (Asosiasi Pengajar Hukum Adat (APHA) Indonesia, Fakultas Hukum Universitas Trisakti - Jakarta Barat, Indonesia, 2017)
This article aims to analyze recognition and respect towards adat law community and adat law in Indonesia legal pluralism context; the strength and weakness of adat law as conflict resolution mechanism; model on state recognition and respect towards adat law community and its adat law in order to reduce the weakness of adat law as a tool to resolve conflict. This is a legal normative article which written based on secondary data, such as books, articles, news, research report, and laws. Collected secondary data are selected based on the issues and analyzed qualitatively. Analysis results on descriptive report which explains the issues comprehensively. This article found that (1) In Indonesia legal pluralism context, the state has not recognized and respect adat law community and its adat law wholeheartedly. It is proven by cumulative limitations which hard to be fulfilled by the adat law community in order to be recognized and respected by the state; (2) The strength of non-litigation conflict resolution based of adat law principles is not about win or lose solution, but about win-win solution. Win-win solution has purpose to achieve justice which acceptable to all parties. Win-win solution is obtained based on consensus from conflicting parties until justice is achieved. The weakness of adat law in Indonesia Law context is the fact that Indonesia adopts European Continental system of law, therefore adat law is not the state law. Adat law is understood by understanding the life of the community where adat law is applied. Adat law is implemented voluntarily, without any force from the state. The weakness of adat law as tool of conflict resolution is the dependency towards good faith between parties. The decision cannot be implemented, unless there is good faith from the conflicting parties; (3) model of adat law community and its adat law recognition and respect is synergic combination model between self declaratory by the adat law community and decisive state recognition with strict limitation which hard to be implemented by the adat law community.